Tlingit potlatch group pose in ceremonial dress, Alaska, ca. 1903 - Hegg, Eric A., 1867-1948
Men pose on steps of building, ca. 1900-1905. One man is in western-style dress, holding a carved panel; the other men are wrapped in blankets with headdresses, holding spears. A woman and some children can be glimpsed in background.